Distribution solutions of some PDEs related to the wave equation and the diamond operator - Chalermpon Bunpog (2018)
In this paper, we find a distribution solution of some PDEs of the operator ⊕ k , defined by (1), which is related to the wave equation and the diamond operator. The existence of the solution to these equations are proven. © 2013 Chalermpon Bunpog.